Preventing Child Delinquency and Crime by Understanding Pancasila Values in Everyday Life - Marisa Kurnianingsih; Avip Rusdi Hananto; Fahmi Fairuzzaman (PT FORMOSA CENDEKIA GLOBAL, 2023)
This socialization activity was carried out aiming to provide direction and provide examples, how to implement Pancasila values ​​that must be applied in everyday life. This is intended to be able to create the next generation of people who are of high quality and have high integrity. So that it can make a positive contribution to the country and bring Indonesia to become a developed country. The existence of Pancasila in the environment can shape the ethics of this nation is really very necessary. With this socialization, participants are expected to be able to listen and receive well the various available information. So that the participants can apply what they have learned and can become a good example among the community, especially for the next generation of young people who will continue the leadership relay in Indonesia.